Telekom Malaysia: Assessing promotion strategies on Integrated Service Digital Network (ISDN) at major business sales Melaka / Norliza Amran - Amran, Norliza (Faculty of Business Management, 2002)
Promotion is very important to many organizations. A good promotion may promise a good feedback from the customers towards the products/services offered by them. This project paper is to assess promotion strategies done by Telekom Malaysia Berhad (TMB) on Integrated Service Digital Network (ISDN) at Major Business Sales (MBS), in Melaka. The objective of this research is to identify what are the current promotion used by TMB in promoting ISDN to the customer and to find out customer's perception towards ISDN's promotion activities and TMB's representative performance. Thus recommendations are included in this project paper in order to help TMB and MBS to increase the effectiveness of the promotion's activities and good performance of the salesperson in promoting the ISDN. In getting a relevant data, 30 questionnaires have been distributed to the selected respondents. The respondents are from MBS customer who are subscribing and not subscribing the ISDN. Data collected were analyzed by using the Statistical Package for Social Science (SPSS) program. The analysis includes the frequency, mean and crosstabulation. The findings reveal that majority of the customers knew about the promotion on ISDN via personal selling and seminar/product updates. It showed us that the current promotion strategies used by TMB on ISDN were those two tools; personal selling and seminar/product updates. This research also found the majority of the respondents said that promotion activities and TMB's representatives' performance were good. But still small number of the respondents said poor. Therefore this project paper revealed the reason why respondents give a different perception towards those questions that have been asked to them through questionnaires. There are few recommendations to TMB and MBS to improve their promotion activities and staff performance in promoting ISDN towards the customer. Hopefully, these recommendations will help them in getting more customers and produce a good/effective salesperson.